Spectroscopic and Photophysical Investigation of Model Dipyrroles Common to Bilins: Exploring Natural Design for Steering Torsion to Divergent Functions - Staheli, Clayton F.; Barney, Jaxon; Clark, Taime R.; Bowles, Maxwell; Jeppesen, Bridger; Oblinsky, Daniel G.; Steffensen, Mackay B.; Dean, Jacob C. (Frontiers in Chemistry, 2021)
Biliproteins are a unique class of photosynthetic proteins in their diverse, and at times, divergent biophysical function. The two contexts of photosynthetic light harvesting and photoreception demonstrate characteristically opposite criteria for success, with light harvesting demanding structurally-rigid chromophores which minimize excitation quenching, and photoreception requiring structural flexibility to enable conformational isomerization. The functional plasticity borne out in these two biological contexts is a consequence of the structural plasticity of the pigments utilized by biliproteins―linear tetrapyrroles, or bilins. In this work, the intrinsic flexibility of the bilin framework is investigated in a bottom-up approach by reducing the active nuclear degrees of freedom through model dipyrrole subunits of the bilin core and terminus free of external protein interactions. Steady-state spectroscopy was carried out on the dipyrrole (DPY) and dipyrrinone (DPN) subunits free in solution to characterize their intrinsic spectroscopic properties including absorption strengths and nonradiative activity. Transient absorption (TA) spectroscopy was utilized to determine the mechanism and kinetics of nonradiative decay of the dipyrrole subunits, revealing dynamics dominated by rapid internal conversion with some Z→E isomerization observable in DPY. Computational analysis of the ground state conformational landscapes indicates enhanced complexity in the asymmetric terminal subunit, and the prediction was confirmed by heterogeneity of species and kinetics observed in TA. Taken together, the large oscillator strengths (f 0.6) of the dipyrrolic derivatives and chemically-efficient spectral tunability seen through the 100 nm difference in absorption spectra, validate Nature's "selection" of multi-pyrrole pigments for light capture applications. However, the rapid deactivation of the excited state via their natural torsional activity when free in solution would limit their effective biological function. Comparison with phytochrome and phycocyanin 645 crystal structures reveals binding motifs within the in vivo bilin environment that help to facilitate or inhibit specific inter-pyrrole twisting vital for protein operation.